Vemurafenib resistance increases melanoma invasiveness and modulates the tumor microenvironment by MMP-2 upregulation. (September 2016) - Sandri, Silvana; Faião-Flores, Fernanda; Tiago, Manoela; Pennacchi, Paula Comune; Massaro, Renato Ramos; Alves-Fernandes, Débora Kristina; Berardinelli, Gustavo Noriz; Evangelista, Adriane Feijó; de Lima Vazquez, Vinicius; Reis, Rui Manuel; Maria-Engler, Silvya Stuchi
Graphical abstract: Abstract: The BRAF V600E mutation confers constitutive kinase activity and accounts for >90% of BRAF mutations in melanoma. This genetic alteration is a current therapeutic target; however, the antitumorigenic effects of the BRAF V600E inhibitor vemurafenib are short-lived and the majority of patients present tumor relapse in a short period after treatment. Characterization of vemurafenib resistance has been essential to the efficacy of next generation therapeutic strategies. Herein, we found that acute BRAF inhibition induced a decrease in active MMP-2, MT1-MMP and MMP-9, but did not modulate the metalloproteinase inhibitors TIMP-2 or RECK in naïve melanoma cells. In vemurafenib-resistant melanoma cells, we observed a lower growth rate and an increase in EGFR phosphorylation followed by the recovery of active MMP-2 expression, a mediator of cancer metastasis. Furthermore, we found a different profile of MMP inhibitor expression, characterized by TIMP-2 downregulation and RECK upregulation. In a 3D spheroid model, the invasion index of vemurafenib-resistant melanoma cells was more evident than in its non-resistant counterpart. We confirmed this pattern in a matrigel invasion assay and demonstrated that use of a matrix metalloproteinase inhibitor reduced the invasion of vemurafenib resistant melanoma cells but not drug naïve cells. Moreover, we did not observe a delimited group of cells invading the dermis in vemurafenib-resistant melanoma cells present in a reconstructed skin model. The same MMP-2 and RECK upregulation profile was found in this 3D skin model containing vemurafenib-resistant melanoma cells. Acute vemurafenib treatment induces the disorganization of collagen fibers and consequently, extracellular matrix remodeling, with this pattern observed even after the acquisition of resistance. Altogether, our data suggest that resistance to vemurafenib induces significant changes in the tumor microenvironment mainly by MMP-2 upregulation, with a corresponding increase in cell invasiveness.